Fatores que influenciam a utilização de artefatos de contabilidade gerencial: um estudo nas empresas cearenses - Campos, Lilian Castelo (2013)
In 1998, the International Federation of Accountants (IFAC) released IMAP 1, a statement on international management accounting practices, recognizing four evolutionary stages in management accounting. Although the publication indicated that management accounting is currently in the fourth stage, studies have shown a low level of implementation of new management accounting techniques in firms and a predominance of traditional rather than modern artifacts. To understand this discrepancy, researchers have attempted to identify factors influencing the use of management accounting artifacts. Much of this research has been based on Institutional and Contingency Theory. Within this perspective, the objective of this study was to evaluate factors potentially influencing the use of management accounting artifacts in the top 100 firms in Ceará according to the 2011 Delmiro Gouveia Award.To do so, the following specific objectives were outlined: (i) characterize the corporate department in charge of management accounting information; (ii) analyze internal contingency factors in organizations, and (iii) identify traditional and modern management accounting artifacts used by the firms in the sample. Based on a survey, the study was descriptive and quantitative. Information was collected through a questionnaire administered to the managers of management accounting information in the top 100 firms in Ceará (according to the 2011 Delmiro Gouveia Award), 56 of whom responded. In general, the comptroller’s office was responsible for management accounting information, primarily through financial performance evaluation, assistance with strategic decisions, and planning. While traditional artifacts were more prevalent than modern artifacts, the difference was smaller than expected. With regard to internal contingency factors, the firms in the sample: i) prioritized strategies of supplying high-quality products and services, pursuing production efficiency, ii) tended to centralize decision making in the hands of the executive director, and iii) needed further IT developments. In conclusion, technology and function influenced the use of traditional management accounting artifacts, while strategy influenced the use of traditional and modern artifacts, confirming the two main hypotheses of the study: H1: The internal contingency factors influence the use of management accounting artifacts in firms in Ceará; and, H2: The corporate department in charge of management accounting information influences the use of management accounting artifacts in firms in Ceará.